2017
DOI: 10.1371/journal.pone.0176385
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant allocation modulates sperm quality across changing social environments

Abstract: In promiscuous species, male reproductive success depends on their ability to mate with fertile females and on the fertilizing ability of their sperm. In such species, theory predicts that, owing to a trade-off between pre- and post-copulatory reproductive traits, males with lesser access to females should increase resource investment into those sperm traits that enhance fertilization success–usually referred to as ejaculate quality. This prediction has been validated in several taxa, yet studies on the physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 78 publications
1
9
3
Order By: Relevance
“…Similar patterns were observed for total sperm length (Additional file 1 : Figure S2). Therefore, our results do not support the hypothesis that sperm morphology is functionally related to sperm swimming ability, and sperm morphology cannot explain the covariation between sperm motility and social status observed previously [ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar patterns were observed for total sperm length (Additional file 1 : Figure S2). Therefore, our results do not support the hypothesis that sperm morphology is functionally related to sperm swimming ability, and sperm morphology cannot explain the covariation between sperm motility and social status observed previously [ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It is worth noting that although older house sparrow males seem to monopolize extra-pair paternities [ 43 ], Møller [ 48 ] has shown that more dominant males obtain more extra-pair copulations. Moreover, we have shown that male House Sparrows occupying different social ranks produce sperm performing differently [ 49 ]. In the current study, we used data from this previous study [ 49 ] and added morphological measurements of spermatozoa to test whether sperm performance is functionally related to sperm morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect that acute aggressive behaviors had on OXY concentrations was much stronger in females than in males (i.e., STI females had 39.62% lower OXY concentrations than control females while STI males had only 6.18% lower OXY concentrations than controls). This sex difference in sensitivity could be given by a differential re-allocation of antioxidants to: protect gametes [61], the developing embryo [see above; 19,56,62], and/or those tissues with the greatest oxygen consumption [e.g., muscles; 59]. Sex differences could also be explained by other physiological pathways besides an increase in activity levels (see below for further discussion).…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the drop in sperm number and/or quality of contest winners reported for the Arctic charr (Rudolfsen Figenschou, Folstad, Tveiten, & Figenschou, 2006) and the domestic fowl (Pizzari, Cornwallis, & Froman, 2007), and the increase of sperm numbers in losers described in the broad-horned flour beetle (Okada, Yamane, & Miyatake, 2010). A strenuous fight may also induce physiological consequences, such as increasing cell oxidative stress levels known to be deleterious to sperm (Tremellen, 2008), with more aggressive males, generally winners, investing less in antioxidants and thus producing lower quality ejaculates (Mora et al, 2017).…”
Section: Introductionmentioning
confidence: 99%